Sistem Informasi Geografis Pemetaan Objek Wisata Wilayah Painan Berbasis Website - Sularno; Aghi Caesar Liandro (Jurnal Kajian Pariwisata Dan Perhotelan, 2023)
The author has conducted research on Objek Wisata in the city of Painan with the aim of finding the location of the Objek Wisata in the city of Painan that is accessed via the web. Thus this geographic information system will display all the locations of Attraction in Painan city, it is expected that the results of the geographical information system of the location of Attraction in Painan can be accessed via the internet using the web. From the results of the data collected, the authors use the Research Laboratory method, which is processing the results of research in a computer laboratory. From the results of this study a geographic information system designed for tourist attractions in the Painan area is web-based. It is hoped that this information system can be useful for people outside the city of Painan when they want to travel and also when the holidays arrive.